The Consensus Hepatitis C Cascade of Care: Standardized Reporting to Monitor Progress Toward Elimination. (28th July 2019) - Safreed-Harmon, Kelly; Blach, Sarah; Aleman, Soo; Bollerup, Signe; Cooke, Graham; Dalgard, Olav; Dillon, John F; Dore, Gregory J; Duberg, Ann-Sofi; Grebely, Jason; Boe Kielland, Knut; Midgard, Håvard; et al.
Abstract: Cascade-of-care (CoC) monitoring is an important component of the response to the global hepatitis C virus (HCV) epidemic. CoC metrics can be used to communicate, in simple terms, the extent to which national and subnational governments are advancing on key targets, and CoC findings can inform strategic decision-making regarding how to maximize the progression of individuals with HCV to diagnosis, treatment, and cure. The value of reporting would be enhanced if a standardized approach were used for generating CoCs. We have described the Consensus HCV CoC that we developed to address this need and have presented findings from Denmark, Norway, and Sweden, where it was piloted. We encourage the uptake of the Consensus HCV CoC as a global instrument for facilitating clear and consistent reporting via the World Health Organization (WHO) viral hepatitis monitoring platform and for ensuring accurate monitoring of progress toward WHO's 2030 hepatitis C elimination targets. Abstract : The Consensus Hepatitis C Cascade of Care is proposed for standardized reporting on progress toward key hepatitis C treatment targets. It provides detailed definitions for 4 essential cascade stages: infected, diagnosed, treated, and cured.